Pandangan Ulama Mazhab (Fuqaha) terhadap Akad Mudharabah dalam Ilmu Fikih dan Penerapannya dalam Perbankan Syariah - Dena Ayu; Mursal Mursal; Doli Witro (Muqaranah, 2022)
Abstract: This paper discusses fuqaha's view of the mudharabah system in fiqh and Islamic banking. This discussion is critical because the mudharabah contract is one of the contracts that can help the community in conducting economic transactions through Islamic banking. This article aims to oversee the mudharabah contract in fiqh and the mudharabah system in Islamic banking. The research method used is the library research method. The research data used is qualitative. The collection is carried out from several sources for reference, such as books, both online and in print, scientific articles downloaded from journals, fatwas from the National Sharia Council of the Indonesian Ulama Council (DSN-MUI), regulations from the Financial Services Authority (OJK) and other data sources. Data analysis techniques used are data condensation, data presentation, and concluding. The results of the analysis show that the mudharabah contract, according to the majority of Fuqaha, is a contract made by two parties who interact with each other, and one of them becomes the investor and surrenders his assets to share/manage, and the profits will be divided according to what has been determined. In Islamic banking, the mudharabah contract is divided into two forms: a system and a product.